Ceramic nanoparticles and carbon nanotubes reinforced thermoplastic materials for piezocapacitive sensing applications - Marinho, T. (2019)
This work reports on the development of polymer composites for load sensing applications. Three thermoplastic polymers, one with elastomeric behaviour, namely poly(styrene-butadiene-styrene) and poly(styrene–ethylene/butylene-styrene), and a semi-crystalline fluorinated polymer, poly(vinylidene fluoride), were selected as hosting matrices. In order to improve the sensing capacity, both ceramic nanoparticles (barium titanate, BT) and carbon nanotubes (CNTs) have been incorporated through solvent mixing followed by spreading the solution onto a glass substrate and subsequent solvent evaporation. Scanning electron microscopy results show that nanoparticles remain uniformly distributed through the nanocomposite at concentrations as high as 50% by weight. Polymer-filler interactions and thermal stability of the nanocomposites were assessed by Fourier transform infrared spectroscopy and thermogravimetric analysis, respectively, in which these nanocomposites present physical interaction between constituents rather than chemical interaction and thermal stability increases slightly for larger filler contents. The mechanical properties are dependent on the matrix, filler type and amount in which the incorporation of both fillers in the elastomeric matrices increases the initial modulus of the nanocomposites up to 3-times. Electrically insulating BT increases dielectric properties and electrically conducting CNTs increase the dc conductivity of nanocomposites, respectively, and the combination of both fillers results in a synergetic effect. Finally, the changes induced by applied static loads on the capacitance variation (ΔC) of the nanocomposites were evaluated, showing a marked enhancement on the ΔC upon the incorporation of both fillers due to the synergetic effect provided by electrically insulating BT together with electrically conducting CNTs.